Penerapan Penerapan Stoisisme Massimo Pigliucci bagi Kaum Muda di Era Modern: Massimo Pigliucci's Application of Stoicism to Young People in the Modern Era - Mardani, Fransiskus Andreas; Pandor, Pius (Undiksha, 2025)
Rapid technological developments and social changes have becomes major challenges for young people in the modern era. The inability to cope with these changes often leads to social pressure, identity crises, and increased suicide rates. This phenomenon highlights the need for an approach that can help young people build mental and moral preparedness to face the changes of the times. This study examines the modern Stoicism of Massimo Pigliucci, which offers practical principles such as the dichotomy of control, self-control, personal reflection, rational thinking, and mental resilience. Although not explicitly aimed at young people, Pigliucci's ideas have proven relevant and applicable in helping them respond to the changes of the times wisely and calmly. This study employs a literature review approach with a descriptive method to analyse the relevance of Pigliucci's philosophy in the context of young people's lives today. The findings indicate that the principles of modern Stoicism can serve as an effective guide for young people in managing life pressures, developing a resilient character, and finding meaning in life amidst the rapid changes of the digital and social era.